How contact with nature affects children’s biophilia, biophobia and conservation attitude in China - Zhang, Weizhe; Goodale, Eben; Chen, Jin (Biological conservation, 2014)
•Chinese school children, ages 9–10, were surveyed across an urbanization gradient.•Mounted specimens were used to measure children’s attitudes towards animals.•We also measured contact with nature and general attitudes towards conservation.•Children’s contact with nature was generally lower in more urban situations.•Contact with nature affected willingness to conserve animals by mediating biophilia. The widening gap between humans and nature, driven by urbanization, seems to be an indisputable fact in the modern world. Such a gap may breed apathy towards environmental concerns and wildlife, which would not bode well for the future of biodiversity conservation. However, the consequences of the decline in physical contact with nature are poorly understood, especially in China, which is urbanizing faster than any other country. In this study, we aimed to understand how contact with nature affects children’s propensity for biophilia and biophobia, and their conservation attitudes. Fifteen schools with different degrees of urbanization were selected and 1119 pupils aged 9–10 filled out questionnaires. The students reported how frequently they engaged in fifteen outdoor activities, and these scores were summed together to produce a measurement of their contact with nature. The participants were shown twelve specimens of common wild animals in order to examine their biophilia and biophobia, and their willingness to conserve animals. We found children from urban schools had less contact with nature than those from rural schools, although this result was only marginally significant because of one outlying rural school. The children’s contact with nature was significantly positively related to their biophilia and negatively related to their biophobia. Children’s biophilia, in turn, significantly affected their willingness to conserve animals, and, to a lesser extent, their general attitudes about conservation. As a whole, the study suggests that contact with nature may enhance children’s willingness to support animal conservation indirectly by nurturing biophilic attitudes to wildlife.